Gender differences in associations of household and ambient air pollution with child health: Evidence from household and satellite-based data in Bangladesh. (April 2020) - Kurata, Masamitsu; Takahashi, Kazushi; Hibiki, Akira
Highlights: Solid fuels for cooking (proxy for household air pollution) is associated with respiratory illness in girls but not boys. Prenatal exposure to ambient PM2.5 correlates with stunting in boys but not girls. Postnatal exposure to ambient PM2.5 is associated with stunting in both genders. Biological and social factors partly explain these contrasting results. To reduce the adverse influences of air pollution on child health, policies should prioritize girls and pregnant women. Abstract: Reduction in health risks from household air pollution (HAP) and ambient air pollution (AAP) is critical for achieving sustainable development globally, especially in low-income countries. Children are at particularly high risk because their respiratory and immune systems are not fully developed. Previous studies have identified the adverse impacts of air pollution on child health. However, most studies do not focus on HAP and AAP simultaneously nor address differences in the timings and magnitudes of prenatal and postnatal exposures across genders. Therefore, this study examines how prenatal and postnatal exposures to ambient particulate matter with aerodynamic diameter of 2.5 μm or less (PM2.5 ) along with household use of solid fuels (a main cause of HAP) are correlated with child health in Bangladesh. We combine individual-level data from nationally representative surveys with satellite-based high-resolution data on ambient PM2.5 . We find that (1) the use of solid fuels is associated with respiratory illness among girls but not boys, (2) prenatal exposure to ambient PM2.5 is associated with stunting in boys but not girls, and (3) postnatal exposure is associated with stunting in both genders. These results provide new evidence for heterogeneous influences of AAP and HAP on child health across gender and timing of exposure. The main policy implications are that interventions against HAP would be more effective by targeting girls, and interventions against AAP should also target pregnant women. In sum, our findings highlight the importance of protecting women from air pollution and achieving Target 3.9 of the Sustainable Development Goals.